The Impact of Individual Ethical Ideology on Situational Strength in the Workplace - Ghazi Abdulredha, Ibtihaa; Hatif Al-Fatlawi , Mithaq (Iraqi Journal for Administrative Sciences, 2026)
This study aims to investigate the effect of individual ethical ideology on situational strength in the workplace by examining the relationship between the two dimensions of ethical ideology (idealism and relativism) and the elements of situational strength (clarity, consistency, constraints, and consequences). The research adopted an analytical approach, both theoretical and empirical. The empirical part was conducted on a random sample of 150 employees from the Directorate of Water Resources in Karbala, using an electronic questionnaire as the primary data collection tool. Data were analyzed through (SPSS V.25) and (AMOS V.23). The results revealed a statistically significant correlation and impact between ethical ideology and situational strength. Employees with an idealistic orientation demonstrated greater alignment with the dimensions of clarity and consistency, whereas those with a relativistic orientation showed more variability in perceiving constraints and consequences. The study highlights the importance of enhancing employees’ ethical awareness and designing training programs that reflect individual value orientations, thereby fostering professional discipline and improving institutional performance.